PENGARUH KUALITAS PRODUKSI TERHADAP KINERJA DAN KEDISIPLINAN KARYAWAN DI PT SIIX ELECTRONICS INDONESIA - Silalahi, Renny; M.M, wasiman S.E (SCIENTIA JOURNAL, 2021)
This study aims to examine the effect of production quality on employee performance and employee discipline at PT Siix Electronics Indonesia.The number of respondents used in this study was 180 respondents. All respondents are employees at PTSiix Electronic Indonesia.Data from the questionnaires were then analyzed using Partial Least Square technique with the help of the Smartpls program. Based on the analytical results in this study,it was found that the quality of production had a positive and significant effect on the performance of employees,this show that the better the quality of the company's production,the better the performance of employees.The results of the second analysis showed that the quality of production was also influentialon employee discipline.Improved company products encourage employees to work more disciplined.